Perceived restorativeness and walkway lighting in near-home environments. (June 2014) - Nikunen, H; Puolakka, M; Rantakallio, A; Korpela, K; Halonen, L
Attention restoration theory (ART) provides fruitful concepts for the investigation of the role of lighting in psychological and attention restoration. The present field study explores the idea that different outdoor lighting qualities may affect the perceived restorativeness of the night-time environment. It studies the relationships between the four components of ART (being away, fascination, extent and compatibility) and perceived lighting attributes (brightness, distribution, glare, colour quality, feeling of safety and pleasantness). Twenty-nine participants rated three walkway lighting environments and twenty-six participants rated two walkway lighting environments in suburban neighbourhoods. Subjective assessments suggested that lighting may have both positive and negative connections with the components of ART. The possible restorative potential of lighting deserves further research attention.